Multidisciplinary support for ethics deliberations during the first COVID wave. (June 2022) - Lombart, Bénédicte; Moïsi, Laura; Bellamy, Valérie; Landolfini, Valérie; Manifacier, Marie-Josée; Mesnage, Valérie; Heilbrunn, Charlotte; Pateron, Dominique; Andro-Melin, Alexandra; Fain, Olivier; Carbonell, Nicolas; Bourrier, Anne; et al.
Background: The first COVID-19 wave started in February 2020 in France. The influx of patients requiring emergency care and high-level technicity led healthcare professionals to fear saturation of available care. In that context, the multidisciplinary E thics- S upport C ell (EST) was created to help medical teams consider the decisions that could potentially be sources of ethical dilemmas. Objectives: The primary objective was to prospectively collect information on requests for EST assistance from 23 March to 9 May 2020. The secondary aim was to describe the Cell's functions during that period. Research design: This observational, real-time study of requests for Cell consultations concerned ethical dilemmas arising during a public health crisis. The EST created a grid to collect relevant information (clinical, patient's/designated representative's preferences and ethical principles strained by the situation), thereby assuring that each EST asked the same questions, in the same order. Participants and research context: Only our university hospital's clinicians could request EST intervention. Ethical considerations: The hospital Research Ethics Committee approved this study (no. CER-2020-107). The patient, his/her family, or designated representative was informed of this ethics consultation and most met with EST members, which enabled them to express their preferences and/or opposition. Findings/results: 33 requests (patients' mean age: 80.8 years; 29 had COVID-19: 24 with dyspnea, 30 with comorbidities). 17 Emergency Department solicitations concerned ICU admission, without reference to resource constraints; others addressed therapeutic proportionality dilemmas. Discussion: Intervention-request motives concerned limited resources and treatment intensity. Management revolved around three axes: the treatment option most appropriate for the patient, the feasibility of implementation, and dignified care for the patient. Conclusions: COVID-19 crisis forced hospitals to envisage prioritization of ICU access. Established decision-making criteria and protocols do not enable healthcare professionals to escape ethical dilemmas. That acknowledgement highlights ethical risks, enhances the added-value of nursing and encourages all players to be vigilant to pursue collective deliberations to achieve clear and transparent decisions.